Peace at all costs : Catholic intellectuals, journalists, and media in postwar Polish-German reconciliation - Frieberg, Annika (2019)
Although it was characterized by simmering international tensions, the early Cold War also witnessed dramatic instances of reconciliation between states, as former antagonists rebuilt political, economic, and cultural ties in the wake of the Second World War. And such efforts were not confined to official diplomacy, as this study of postwar rapprochement between Poland and West Germany demonstrates. Drawing on a wide range of sources, Peace at All Costs follows Polish and German non-state activists who attempted to establish dialogue in the 1950s and 1960s, showing how they achieved modest successes and media attention at the cost of more nuanced approaches to their national histories and identities.